2012
DOI: 10.1007/s00213-012-2732-y
|View full text |Cite
|
Sign up to set email alerts
|

A placebo-controlled study to assess Standardized Field Sobriety Tests performance during alcohol and cannabis intoxication in heavy cannabis users and accuracy of point of collection testing devices for detecting THC in oral fluid

Abstract: RationaleStandardized Field Sobriety Tests (SFST) and oral fluid devices are used to screen for driving impairment and roadside drug detection, respectively. SFST have been validated for alcohol, but their sensitivity to impairment induced by other drugs is relatively unknown. The sensitivity and specificity for Δ9-tetrahydrocannabinol (THC) of most oral fluid devices have been low.ObjectiveThis study assessed the effects of smoking cannabis with and without alcohol on SFST performance. Presence of THC in oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 22 publications
3
55
2
1
Order By: Relevance
“…Similarly, diagnostic sensitivity, specificity, and efficiency improved in occasional and frequent smokers when considering samples collected up to 6 or 8h post dose, due to the higher incidence of true positive tests. This is consistent with two prior studies that documented higher sensitivities in samples collected recently after smoking [18,12]. …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similarly, diagnostic sensitivity, specificity, and efficiency improved in occasional and frequent smokers when considering samples collected up to 6 or 8h post dose, due to the higher incidence of true positive tests. This is consistent with two prior studies that documented higher sensitivities in samples collected recently after smoking [18,12]. …”
Section: Discussionsupporting
confidence: 93%
“…and A-Concateno DDS devices achieved ≥80% efficiency, sensitivity was only 69.2% and 37.8%, respectively. Overall, the authors concluded that the DrugTest 5000 achieved the best diagnostic efficiency for OF cannabinoids detection [13,17,16,18]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported the low sensitivity of saliva screening tests for benzodiazepines 44,46 and for marijuana 43,46,47 in field settings. This was reflected in the findings of the current study.…”
Section: Discussion and Limitationsmentioning
confidence: 94%
“…In order to increase the sensitivity of SFSTs for THC, the addition of some tests and observations has been suggested, such as "head movements or jerks" (Papafotiou et al, 2005a(Papafotiou et al, , 2005b or a series of observations conducted by the physician as part of the Norwegian clinical test of impairment . Even with these extra observations, however, THC impairment is difficult to detect, particularly at lower THC concentrations (Bosker et al, 2012).…”
Section: Introductionmentioning
confidence: 99%